Insights Into the Concept of Rheumatoid Arthritis Flare - Bozzalla-Cassione, Emanuele; Grignaschi, Silvia; Xoxi, Blerina; Luvaro, Terenzj; Greco, Maria Immacolata; Mazzucchelli, Iolanda; Bugatti, Serena; Montecucco, Carlomaurizio; Manzo, Antonio (Frontiers in Medicine, 2022)
Identification of a pathological change in course of systemic chronic immune-inflammatory diseases is key to deliver effective treatment strategies. In this context, one of the most compelling issues is the concept of flare. The multifaceted expression of disease activity in rheumatoid arthritis (RA) makes it difficult to provide an omni-comprehensive definition of flare, able to encompass the different objective and subjective domains of the pathology. Our incomplete understanding of the pathophysiological mechanisms underlying this process contributes further to the partial comprehension of its potential clinical expression. In this review we focus on the proposed pathophysiological processes underlying disease recrudescence in RA and on the variable definitions that have been adopted to capture flare in clinical practice through its objective, subjective and temporal domains. What emerges, overall, is a complex landscape far from being unraveled.